2013
DOI: 10.1088/2040-8978/15/9/094007
|View full text |Cite
|
Sign up to set email alerts
|

Polarized light imaging of birefringence and diattenuation at high resolution and high sensitivity

Abstract: Polarized light microscopy provides unique opportunities for analyzing the molecular order in man-made and natural materials, including biological structures inside living cells, tissues, and whole organisms. 20 years ago, the LC-PolScope was introduced as a modern version of the traditional polarizing microscope enhanced by liquid crystal devices for the control of polarization, and by electronic imaging and digital image processing for fast and comprehensive image acquisition and analysis. The LCPolScope is … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
105
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 108 publications
(105 citation statements)
references
References 30 publications
0
105
0
Order By: Relevance
“…The development and refinement of polarized light microscopy measurements to study changes in the organization of molecular components in individual cells has had many applications in cell biology and beyond [4,31,32]. To study the bioaccumulation of small molecule drugs inside cells, the experiments presented here indicate how a quantitative multiparameter imaging system combining polarization, transmittance and fluorescence measurements can be useful for studying the cellular mechanisms of drug disposition from the cellular to the molecular level.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The development and refinement of polarized light microscopy measurements to study changes in the organization of molecular components in individual cells has had many applications in cell biology and beyond [4,31,32]. To study the bioaccumulation of small molecule drugs inside cells, the experiments presented here indicate how a quantitative multiparameter imaging system combining polarization, transmittance and fluorescence measurements can be useful for studying the cellular mechanisms of drug disposition from the cellular to the molecular level.…”
Section: Discussionmentioning
confidence: 99%
“…Polarization measurements are acquired utilizing the diattenuation LC-PolScope microscope, a custom built microscopic imaging system similar to the birefringence LC-PolScope designed by Oldenbourg et al [4], but without the polarization analyzer. Our LC-PolScope is built on the Nikon Eclipse Ti inverted microscope (Nikon Instruments, Melville, New York), with the computer-controlled universal compensator (Hinds Instrumentation, Hillsboro, Oregon) placed between the interference filter (623 ± 23 nm, Semrock Optics, Rochester, New York) and condenser lens (Fig.…”
Section: Multi-parameter Imaging Instrument Set Upmentioning
confidence: 99%
See 1 more Smart Citation
“…The main advantage of LC-Polscope compared to traditional polarizing microscopes is that it can measure the retardance or diattenuation along with their dominant orientation simultaneously at all points of the image without having to mechanically rotate the specimen. Note that the birefringence measurement is affected by the diattenuation, but the diattenuation is sensitive only to differential transmittance, as detailed in Mehta et al 23 and demonstrated for reduced-GO in Tkacz et al 24 In the two extreme cases of pH 1 and 14, the suspensions did not form liquid crystals at any concentration due to aggregation of GO platelets (see S2 in ESI for further details). At pH 2, 6, and 9, a complete phase separation was observed after 4-6 days, with I phase at the top and N phase at the bottom of the capillary.…”
mentioning
confidence: 87%
“…Polarized light imaging/spectroscopy has been comprehensively investigated for tissue diagnosis [6][7][8][9][10][11][12][13][14][15][16][17]. Polarized light implementation offers several compelling advantages as follows: (i) surface and beneath-the-surface detection of biological tissue taken from the tissue depolarization properties [11,15]; (ii) tissue anisotropy analysis through the tissue diattentuation and retardance [13,14]; (3) enhanced tissue diagnosis through the combination of complementary depolarization, diattentuation and retardance of the tissues [9].…”
Section: Introductionmentioning
confidence: 99%